Casting Revealed, 2nd Edition - Schell, Hester (Routledge, 2016)
Casting is an essential component of any film or video project, but the core skill-set needed to cast effectively is little understood. Casting Revealed: A Guide for Film Directors is a straightforward manual on the art and craft of casting. Here, director Hester Schell offers her insider perspective on casting workflows, industry standards, finding actors, running auditions, what to look for in a performance, contracts, and making offers. This new edition has been updated with fresh interviews with casting directors, full color head shots, new information about online video submissions, and a companion website featuring forms, contracts, and sample scenes for auditions. Gain a fuller understanding of the misunderstood art and craft of casting actors for film and video production. Learn to find the right actors for any production, run auditions, interview actors, effectively judge performances and video submissions, evaluate suitability for a role, discover what it is you need from an actor, view headshots, draft contracts, make offers, and navigate current industry standards, unions, and procedures. This new edition has been updated to include full color sample head shots, new content on online video submissions, listings of casting wesbites, film resources, and film commissions and a companion website featuring interviews with celebrated casting directors from New York, Portland, Boston and Austin, necessary forms, sign-in sheets, contracts, and sample scenes for auditions.